2020
DOI: 10.1002/ece3.7040
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the South Australian Macrobenthic Traits (SAMT) database: A trait classification for functional assessments

Abstract: Trait-based approaches have become topical in ecological research for understanding the relationship between species (biodiversity) and ecosystem functioning, ecosystem processes, ecosystem services, or responses to anthropogenic disturbances (Bolam et al., 2016;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The functional traits selected describe behavioral, morphological, and physiological attributes of benthic macrofauna, and are considered as effects traits as they are directly or indirectly related to several ecosystem functions including nutrient cycling and sediment transport (Lam-Gordillo et al, 2020a). Trait information was obtained from the South Australia Macrobenthic Trait (SAMT) database (Lam-Gordillo et al, 2020b). The SAMT database applied a fuzzy coding procedure assigning scores from 0 to 1, with 0 being no affinity and 1 being high affinity to a trait (for details see Lam-Gordillo et al, 2020b).…”
Section: Selection Of Traits and Trait Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…The functional traits selected describe behavioral, morphological, and physiological attributes of benthic macrofauna, and are considered as effects traits as they are directly or indirectly related to several ecosystem functions including nutrient cycling and sediment transport (Lam-Gordillo et al, 2020a). Trait information was obtained from the South Australia Macrobenthic Trait (SAMT) database (Lam-Gordillo et al, 2020b). The SAMT database applied a fuzzy coding procedure assigning scores from 0 to 1, with 0 being no affinity and 1 being high affinity to a trait (for details see Lam-Gordillo et al, 2020b).…”
Section: Selection Of Traits and Trait Informationmentioning
confidence: 99%
“…Trait information was obtained from the South Australia Macrobenthic Trait (SAMT) database (Lam-Gordillo et al, 2020b). The SAMT database applied a fuzzy coding procedure assigning scores from 0 to 1, with 0 being no affinity and 1 being high affinity to a trait (for details see Lam-Gordillo et al, 2020b). This resulted in the compilation of three data matrices (1) "taxa abundance by site matrix, " in this case the data collected from our surveys; (2) "taxa by traits matrix, " obtained from the SAMT database; and (3) the combinations of the previous two: "traits by site matrix" (Bremner et al, 2006;Bremner, 2008).…”
Section: Selection Of Traits and Trait Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bhowmik & Mandal, 2021; Bremner et al., 2003; D'Alessandro et al., 2020; Van der Linden et al., 2012, 2016; Zhong et al., 2020), although an increase in the number of studies carried out in estuaries in tropical regions has been observed in recent times (e.g. Duarte et al., 2020; Lam‐Gordillo et al., 2020; Medeiros, Heino, et al., 2021; Medeiros, Paiva, et al., 2021; Van der Linden et al., 2017; Wouters et al., 2018). In general, these studies aim to understand how environmental characteristics affect benthic community functions in estuaries.…”
Section: Introductionmentioning
confidence: 99%
“…Trait-based studies have covered various aquatic taxa, such as phytoplankton (Pálffy et al, 2013;Du et al, 2022), periphyton (Bichoff et al, 2018;Wang et al, 2022), zooplankton (Kuczyńska-Kippen et al, 2020;Shen et al, 2022), macroinvertebrates (Pallottini et al, 2017;Belmar et al, 2019), and fish (Brind'Amour et al, 2011;Toussaint et al, 2016). They have also examined diverse geographic regions, including North America (Boucek and Rehage, 2014;Sinclair et al, 2021), Europe (Belmar et al, 2019;Wu et al, 2019), Australia (Galego de Oliveira et al, 2019;Lam-Gordillo et al, 2020), and Asia (Matsuzaki et al, 2016;Wang et al, 2022). Functional diversity is generally governed by two deterministic processes underlying community assembly (Mouchet et al, 2010).…”
Section: Introductionmentioning
confidence: 99%